KINETIKA PENGERINGAN CABE JAMU MENGGUNAKAN PENGERING EFEK RUMAH KACA BERBANTU PENYIMPAN PANAS - Mu'tamar, Mohammad Fuad Fauzul; Firmansyah, Arief; Firmansyah, Dhefanie (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Solar greenhouse drying could become an alternative drying technique that is affordable, applicable, and safe. However, it is solar-dependent. Thus, it requires a system that supplieses heat during the absence of solar energ; using This research aims to determine the drying kinetics of cabe jamu using a solar greenhouse dryer assisted by heat storage. The object of this research was cabe jamu, which is categorized as a predominant Madura agriculture product. The drying was held for 3 days, and the observation parameters were length, diameter, and mass during drying. Material that is used as heat storage was black shinning Lumajang sand. During the the drying process, ambient temperature, solar greenhouse temperature, and sand temperature were read every 1 h. The result showed that Midilli and Kucuk model have a good-fitting performance to portray the drying kinetics of cabe jamu assisted by and without heat storage. The result also confirms that application of heat storage to solar greenhouse dryer did not shorten drying time; otherwise, increase the percentages of product volume shrinkage.